2020
DOI: 10.1111/apa.15376
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis of paediatric appendicitis during the COVID‐19 pandemic

Abstract: Since it was first detected, novel coronavirus disease rapidly spread, striking over 4 million people worldwide. 1 While adults with COVID-19 demonstrate a range of disease severity with 20% of infected adults being critically ill and an estimated fatality rate as high as 2%, children mostly suffer from a mild disease, only minority presenting with respiratory distress syndrome or multi-organ failure. [2][3][4] However, the role of infected children in spreading the virus to their older relatives and caregive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
190
8
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(233 citation statements)
references
References 11 publications
18
190
8
17
Order By: Relevance
“…[5] Our study showed almost similar rates of perforation though there was slight increase in perforation rates in group B by six percent comparing to group A patients (14.2% vs 20 %) while total complicated cases increased by around 7 % (16.67 % vs 24 %). Snapiri et al [9] showed total complicated rates of 22 % during COVID times which was similar to study by Tankel et al [6] Overall prevalence of fecalith was 9.5 % in our study in which 16.67 % of perforations in group A and 60 % of perforations in group B were fecalith induced. The prevalence rate was somehow similar to study from West Indies by Ramdass et al [10] where fecaliths were present in 13.6% of the appendectomy specimens.…”
Section: Discussionsupporting
confidence: 90%
“…[5] Our study showed almost similar rates of perforation though there was slight increase in perforation rates in group B by six percent comparing to group A patients (14.2% vs 20 %) while total complicated cases increased by around 7 % (16.67 % vs 24 %). Snapiri et al [9] showed total complicated rates of 22 % during COVID times which was similar to study by Tankel et al [6] Overall prevalence of fecalith was 9.5 % in our study in which 16.67 % of perforations in group A and 60 % of perforations in group B were fecalith induced. The prevalence rate was somehow similar to study from West Indies by Ramdass et al [10] where fecaliths were present in 13.6% of the appendectomy specimens.…”
Section: Discussionsupporting
confidence: 90%
“…9,10 Our findings are in accordance with a recent report by Snapiri et al In their study they describe seven pediatric patients that received late diagnosis of acute appendicitis which resulted in higher rates of complications, such as perforated appendix and/or peri-appendicular abscess formation. 11 The authors recognized parental concern of contracting COVID-19 in places like the ER as a potential reason for the delayed possible explanation for the decrease in the number of acute appendicitis patients noted in our study could be the decreasing incidence of acute appendicitis in Western countries and its seasonal variation. In the United States the incidence of perforated and nonperforated acute appendicitis, as well as the number of appendectomies performed has been decreasing in recent years.…”
Section: Discussionmentioning
confidence: 65%
“…Some authors have proposed that milder forms can be treated conservatively at home [15] or using antibiotics [9]. Snapiri et al also reported delays in diagnosing AA in seven pediatric patients having complicated forms of AA [16]. We believe that other factors may contribute to the decrease including various infectious agents (viruses, bacteria, fungi and parasites) whose exposure in the pediatric population and a potential link to AA have been proposed [17,18].…”
mentioning
confidence: 92%